Inovasi Teknologi Pengolahan Urin Kelinci Menjadi Pupuk Organik Cair : Perspektif Kewirausahaan dalam Peternakan Berkelanjutan - Edya Moelia Moeis; Mukhlison Mukhlison; Meisya Alma Azizah (Lembaga Pengembangan Kinerja Dosen, 2025)
The growing demand for organic fertilizers as an alternative to chemical fertilizers is in line with increasing public awareness of environmentally friendly agriculture. Meanwhile, livestock waste, particularly rabbit urine, remains underutilized and is often discarded, despite its high nitrogen, phosphorus, and potassium content and potential as a raw material for liquid organic fertilizer (LOF). This study aims to design and develop a simple technological innovation for processing rabbit urine into economically valuable LOF, offering new business opportunities for local communities. Another objective is to advance bioactivator-based processing technology to produce an effective, marketable, and eco-friendly organic fertilizer that enhances plant growth. The research employed an applied research method with an experimental approach, including collection and processing of rabbit urine, simple production of LOF, effectiveness testing on horticultural crops with local farmers, and analysis of business feasibility and local marketing strategies. The study resulted in a simple bioactivator-based technology for converting rabbit urine into LOF through a fermentation process of more than 14 days, producing fertilizer rich in nitrogen, phosphorus, and potassium. The LOF improved horticultural crop growth by 25–30% compared to control plants. The group business model provides livestock farmers with new business opportunities, achieving profit margins between 40% and 50%. This research produced a replicable technology guide and usable LOF product, contributing to waste reduction and supporting sustainable agriculture through community-based entrepreneurship.